Stressful university life : the relationship among academic self-efficacy, social comparison orientation, academic performance, goal characteristics, and psychological well-being of university students in Singapore. - Lim, Suu Yue. (2010)
The goal of this study is to examine how the well-being of university students in Singapore is influenced by academic concerns. In particular, we investigate the relationship among academic self-efficacy, social comparison orientation, academic performance, goal characteristics (i.e., ideal GPA, goal importance, goal motivation, GPA difference), and psychological well-being (i.e., depression and satisfaction with life). Our theoretical model, which integrates these concepts, provides fruitful insight to better understand the well-being of university students. A self-administered paper-and-pencil survey was conducted with 603 final-year undergraduate students from the two public autonomous universities in Singapore: National University of Singapore (NUS) and Nanyang Technological University (NTU). Our analyses indicated that academic self-efficacy has both a direct and indirect relationship with students’ levels of depressive symptoms and satisfaction with life. Specifically, academic self-efficacy was found to negatively predict students’ levels of depressive symptoms and positively predict their satisfaction with life. The relationship between students’ academic self-efficacy and their level of depressive symptoms was also found to be mediated by goal importance, goal motivation, and GPA difference. Similarly, the relationship between academic self-efficacy and satisfaction with life was found to be mediated by goal importance. In addition, academic self-efficacy was a significant predictor of academic performance, ideal GPA, goal importance, goal motivation, and GPA difference. Furthermore, students’ social comparison orientation was found to be a significant positive predictor of students’ levels of depressive symptoms, academic performance, goal importance, and ideal GPA. Consequently, theoretical and practical implications of our findings are discussed.